2004
DOI: 10.1001/archinte.164.3.262
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin Alfa

Abstract: Recombinant human erythropoietin (epoetin alfa) has been used in clinical settings for more than a decade. Its indications have expanded considerably from its original use as hormone therapy in the treatment of anemia in adults with chronic kidney disease. Since the introduction of epoetin alfa, a greater understanding of anemia pathophysiology and the interactions of erythropoietin, iron, and erythropoiesis has been elucidated. Anemia is now independently associated with increased mortality and disease progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(11 citation statements)
references
References 187 publications
1
10
0
Order By: Relevance
“…Recombinant erythropoietin (rHuEPO) is widely used in clinical practice in the treatment of several types of anaemia [1,2,3,4]. We observed that patients with end-stage multiple myeloma (MM) treated with EPO live longer than expected, despite their original poor prognostic features [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant erythropoietin (rHuEPO) is widely used in clinical practice in the treatment of several types of anaemia [1,2,3,4]. We observed that patients with end-stage multiple myeloma (MM) treated with EPO live longer than expected, despite their original poor prognostic features [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the conventional erythropoietic activity, EPO was recently identified as a pleiotropic organ-protective cytokine [1013]. Because of the resolution of myocardial stunning and reperfusion injury, the LV ejection fraction (LVEF), a powerful prognostic parameter improves steeply during the first week after MI [25, 26].…”
Section: Resultsmentioning
confidence: 99%
“…During the last two decades, the clinical indications of rHuEPO have been expanded to anemia in diverse clinical categories, including anemic patients with chronic kidney disease [10]. Beyond the conventional effect of secreted erythropoietin from the kidney in response to hypoxic stimuli, EPO was recently identified as a pleiotropic and organ-protective cytokine, mediating repair and regeneration via anti-apoptosis, anti-inflammation, anti-oxidation, pro-angiogenesis and re-endothelialization, vascular-protectant, mobilization of endothelial progenitor cells, and recruitment of stem cells into the zone of damage [1013]. Apart from traditional erythropoietic effects, the pleiotropic organ-protective effects of erythropoietin (EPO) make it a frontline cardioprotective candidate[11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, attempts are currently under way to develop a wide variety of therapeutic proteins for treating conditions such as cancer, infectious diseases, and autoimmune disorders. 48) …”
Section: Introductionmentioning
confidence: 99%